2013
DOI: 10.1017/jfm.2013.330
|View full text |Cite
|
Sign up to set email alerts
|

Numerical calculations of two-dimensional large Prandtl number convection in a box

Abstract: Convection from an isolated heat source in a chamber has been previously studied numerically, experimentally and analytically. These have not covered long time spans for wide ranges of Rayleigh number Ra and Prandtl number Pr. Numerical calculations of constant viscosity convection partially fill the gap in the ranges $\mathit{Ra}= 1{0}^{3} {{\unicode{x2013}}}1{0}^{6} $ and $\mathit{Pr}= 1, 10, 100, 1000$ and $\infty $. Calculations begin with cold fluid everywhere and localized hot temperature at the centre o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
12
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
4
1
1

Relationship

3
3

Authors

Journals

citations
Cited by 11 publications
(20 citation statements)
references
References 18 publications
3
12
0
Order By: Relevance
“…The numerical simulations of Whitehead et al (2013) show that when the Prandtl number is greater than ⇠ 10 3 , the dynamics of thermal plumes are essentially identical to those calculated at an infinite Prandtl number, confirming that our experiments are relevant to the mantle.…”
Section: Methodssupporting
confidence: 74%
“…The numerical simulations of Whitehead et al (2013) show that when the Prandtl number is greater than ⇠ 10 3 , the dynamics of thermal plumes are essentially identical to those calculated at an infinite Prandtl number, confirming that our experiments are relevant to the mantle.…”
Section: Methodssupporting
confidence: 74%
“…Whether the perturbation grows or decays is easily viewed by subtracting out the original linear distributions of T and C. In all cases, flows have the same qualitative structure irrespective of grid size and only the quantitative values change a little. This result is also found for plume studies (Whitehead et al 2013). Benchmark calculations with different grid sizes (in parenthesis) and a time step of 10 −6 with Raf = 0 give the four critical values Rac = 805 (32), 791 (64), 782 (128), and 780 (256).…”
Section: Heated From Below Stabilizing Flux Of Compositionsupporting
confidence: 72%
“…The rectangular grid is two-dimensional with 128 points on a side giving an accuracy of 1 part in 10 6 . Resolution was tested as in an earlier study (Whitehead et al 2013) and all extrema of the fields are accurate to better than 1%. Since C has only flux boundary conditions, there is a slow random drift in the spatially averaged value of concentration C within the chamber over long times.…”
Section: Methodsmentioning
confidence: 99%
“…For most runs the continent starts on the far right, but trial runs with other initial locations produce no change in properties reported here. The procedure has equation advanced numerically in time [ Whitehead et al ., ] using a leapfrog‐trapezoidal scheme. Then equation is solved by inverting the Poisson equation, and equation is solved the same way.…”
Section: Methodsmentioning
confidence: 99%